2021
DOI: 10.1016/j.ebiom.2021.103721
|View full text |Cite
|
Sign up to set email alerts
|

Grandmaternal cells in cord blood

Abstract: Background: During pregnancy a feto-maternal exchange of cells through the placenta conducts to maternal microchimerism (Mc) in the child and fetal Mc in the mother. Because of this bidirectional traffic of cells, pregnant women have also acquired maternal cells in utero from their mother and could transfer grandmaternal (GdM) cells to their child through the maternal bloodstream during pregnancy. Thus, cord blood (CB) samples could theoretically carry GdMMc. Nevertheless this has never been demonstrated. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Additional outstanding questions remain regarding why the repertoire of exceptionally rare microchimeric cells is not expandable, especially considering their numerical and cellular interindividual variability during embryonic development ( 38 , 39 ) and protective role against early life infection ( 40 ). Given increased circulating MMc levels in women during pregnancy ( 41 ) and recent identification of grandmaternal microchimeric cells in first-pregnancy specimens from cord blood ( 42 ), purposeful MMc displacement to further extend tolerance to grandchildren represents a provocative explanation that requires further evaluation. Collectively, these results regarding how pregnancy affects the outcomes of future pregnancies in mothers and their daughters reveal distinctions in how familial antigens are immunologically remembered and how tolerance to fetal alloantigens is naturally optimized to improve pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional outstanding questions remain regarding why the repertoire of exceptionally rare microchimeric cells is not expandable, especially considering their numerical and cellular interindividual variability during embryonic development ( 38 , 39 ) and protective role against early life infection ( 40 ). Given increased circulating MMc levels in women during pregnancy ( 41 ) and recent identification of grandmaternal microchimeric cells in first-pregnancy specimens from cord blood ( 42 ), purposeful MMc displacement to further extend tolerance to grandchildren represents a provocative explanation that requires further evaluation. Collectively, these results regarding how pregnancy affects the outcomes of future pregnancies in mothers and their daughters reveal distinctions in how familial antigens are immunologically remembered and how tolerance to fetal alloantigens is naturally optimized to improve pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) in detecting GFP +/− maternal cells. Furthermore, to prevent detection of GFP-positive grand-maternal cells 39 , the mother mice were obtained by crossing BALB/cByJJcl wild-type female mice with GFP -homozygous male mice. MHC types of mice were carefully designed for utility to concentrate MMc cells using magnetic cell sorting system (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Coincidentally, a naturally occurring human model for transgenerational (T) cells also exists, whereby cells are passed from mother to child during pregnancy and have been shown to survive in the offspring for extended periods 7 . Some studies even suggest that grandmaternal cells can be found in umbilical cord blood of second‐generation offspring 8 . A point of debate regarding the purpose of these long‐lived cells has always been the matter of location.…”
Section: Figurementioning
confidence: 99%
“…7 Some studies even suggest that grandmaternal cells can be found in umbilical cord blood of secondgeneration offspring. 8 A point of debate regarding the purpose of these long-lived cells has always been the matter of location. Why would these cells circulate systemically instead of homing to their target tissue?…”
mentioning
confidence: 99%